2019
DOI: 10.1001/jamaoto.2018.4077
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Cheyne-Stokes Breathing After Hypoglossal Nerve Stimulator Implant in a Patient With Mixed Sleep Apnea

Abstract: Fleming JJ. The decline of venture capital investment in early-stage life sciences poses a challenge to continued innovation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Further details on his postoperative course are discussed in a separately published case report. 18 Patient 18 experienced a dramatic reduction in his AHI from 102.9 to 30.8 events/hour on titration PSG, with a CAI of 5.4 events/hour and obstructive AHI of 25.4 events/hour. This patient had both central and obstructive respiratory events on baseline PSG, a phenotype of OSA that is associated with high loop gain and sleep instability.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Further details on his postoperative course are discussed in a separately published case report. 18 Patient 18 experienced a dramatic reduction in his AHI from 102.9 to 30.8 events/hour on titration PSG, with a CAI of 5.4 events/hour and obstructive AHI of 25.4 events/hour. This patient had both central and obstructive respiratory events on baseline PSG, a phenotype of OSA that is associated with high loop gain and sleep instability.…”
Section: Discussionmentioning
confidence: 93%
“…Our multi‐disciplinary team believed that the central apneas might resolve with adequate treatment by HGNS and thus surgery was offered to this patient. Further details on his postoperative course are discussed in a separately published case report . Patient 18 experienced a dramatic reduction in his AHI from 102.9 to 30.8 events/hour on titration PSG, with a CAI of 5.4 events/hour and obstructive AHI of 25.4 events/hour.…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, Chan et al first observed that one patient had a significantly increased CSA during titration. Both OSA and CSA were resolved after the patient’s device configuration was changed to unipolar stimulation and amplitude was calibrated from 0.6 to 1.6 V. In 2019, Sarber et al 3 reported a patient with mixed sleep apnea (CAI of 12.5 event/h) who presented with a TECSA (CAI of 78.9 event/h) and obstructive apnea and hypopnea index of 4.9 event/h with Cheyne-Stokes breathing (CSB) after implantation of HNS. During follow-up, the CSA and CSB continued throughout the study without HNS activation.…”
Section: Discussionmentioning
confidence: 99%
“…1 Nevertheless, a few case reports and one retrospective study reported elevated central sleep apnea (CSA), which has been indicated as an independent predictor of heart failure and could lead to significant comorbidity and an increased risk of adverse cardiovascular outcomes. [2][3][4][5] In 2020, the International Classification of Sleep Disorders-third edition introduced the term "TECSA" (Treatment-Emergent Central Sleep Apnea) and defined it as the presence of primary OSA at the initial diagnostic sleep study, significant resolution of obstructive events with CPAP titration followed by emergence or persistence of central events during PAP treatment with a central apnea index (CAI) ≥5/h, >50% of events being central, and symptoms that cannot be explained in a better manner by another CSA disorder. 6 However, the evidence of TECSA following HNS is limited, especially for the long-term observations.…”
Section: Introductionmentioning
confidence: 99%